2019
DOI: 10.1515/dmpt-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Drug S-oxidation and phenylalanine hydroxylase: a biomarker for neurodegenerative susceptibility in Parkinson’s disease and amyotrophic lateral sclerosis

Abstract: Background The S-oxidation of S-carboxymethyl-L-cysteine has been reported previously to be a biomarker of disease susceptibility in Parkinson’s disease and amyotrophic lateral sclerosis. In the present investigation, the original observations have been extended and confirmed. Methods Meta-analysis of previously published investigations into the S-oxidation polymorphism together with new subject data was evaluated. Results The incidence of the poor metaboliser phenotype (no urinary recovery of S-oxide meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Additionally, another study found that the tyrosine/phenylalanine ratio in PD patients is lower than that in controls ( Hirayama et al, 2016 ), this suggests that the metabolic pathway of phenylalanine (through PAH) in PD may shift to another one that does not end by tyrosine. Indeed, recently PD patients showed lower activity in their PAH enzyme ( Steventon and Mitchell, 2018 ; Rawlings et al, 2019 ). All these studies support our hypothesis that the metabolism of phenylalanine in PD patients is altered via the following mechanisms: 1) reduction of PAH activity, which results in metabolizing phenylalanine through the PAL metabolic pathways, thus, reducing the production of tyrosine, and, subsequently, dopamine and norepinephrine; 2) enhancing PAL activity with the resultant increase in the production of trans-cinnamate and ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another study found that the tyrosine/phenylalanine ratio in PD patients is lower than that in controls ( Hirayama et al, 2016 ), this suggests that the metabolic pathway of phenylalanine (through PAH) in PD may shift to another one that does not end by tyrosine. Indeed, recently PD patients showed lower activity in their PAH enzyme ( Steventon and Mitchell, 2018 ; Rawlings et al, 2019 ). All these studies support our hypothesis that the metabolism of phenylalanine in PD patients is altered via the following mechanisms: 1) reduction of PAH activity, which results in metabolizing phenylalanine through the PAL metabolic pathways, thus, reducing the production of tyrosine, and, subsequently, dopamine and norepinephrine; 2) enhancing PAL activity with the resultant increase in the production of trans-cinnamate and ammonia.…”
Section: Discussionmentioning
confidence: 99%
“…Also, integrins are play important role pathophysiology of many brain diseases, such as epilepsy, and consider a potential target for the discovery of new drugs for neurological disorders [11,12] different biomarkers are currently being studied in Alzheimer disease and other neurodegeneration diseases such as cerebrospinal fluid (CSF) Aβ, tau, phosphorylated tau and the other neuronal proteins, PET tracers for Aβ, tau and glucose uptake, and MR measures of brain diseases [13][14][15]. Interestingly, phenylalanine hydroxylase could also be a biomarker of neurodegenerative disease [16] (Figure 2). The only promising in prevention and delay neurodegenerative diseases are many herbal plants that have been studied like Nigella sativa (Khazdair, 2015), moringa olifera [17] and many Plants-derived natural products used in the treatment of neurological diseases [18].…”
Section: Introductionmentioning
confidence: 99%